Effectiveness of vortioxetine for major depressive disorder in real-world clinical practice: US cohort results from the global RELIEVE study - Mattingly, Gregory; Brunner, Elizabeth; Chrones, Lambros; Lawrence, Debra F.; Simonsen, Kenneth; Ren, Hongye (Frontiers in Psychiatry, 2023)
Introduction: Effective treatment of major depressive disorder (MDD) involves addressing both depressive and functional symptoms, increasing patients’ overall sense of well-being and quality of life (QoL). Methods: RELIEVE was an international observational, prospective study in patients ≥18 years with a current diagnosis of a major depressive episode (MDE) initiating vortioxetine in routine clinical practice; outcomes for participants from the United States are presented here. Functioning was assessed at weeks 12 and 24 versus baseline using the Sheehan Disability Scale (SDS). Secondary effectiveness analyses assessed changes from baseline to weeks 12 and 24 in functioning, depression severity, cognitive symptoms, sexual function, and QoL. Results: Participants had an average of 8.2 previous MDEs; mean duration of their current MDE at baseline was 93.5 weeks. Vortioxetine was used as second- or later-line treatment for 80.5% of participants. Least-squares mean (SE) SDS total score significantly decreased from baseline by 7.19 (0.52) points at week 12 and 8.19 (0.56) points at week 24 (P < 0.0001 for both). Significant improvements were also reflected across SDS subscores, depression severity, cognitive function, sexual function, and QoL. Healthcare resource utilization and productivity parameters also improved. Adverse events were observed in 21.8% of patients, with nausea being the most common (7.3%). Conclusion: This real-world study demonstrated improvements in functioning, depressive symptoms, and cognitive function in patients with MDD treated with vortioxetine in routine clinical practice in the United States. Outcomes were consistent with the efficacy and safety profile of vortioxetine in randomized controlled trials.